2005
DOI: 10.1002/jobm.200510007
|View full text |Cite
|
Sign up to set email alerts
|

Growth ofEnterococcus mundtii ST15 in medium filtrate and purification of bacteriocin ST15 by cation-exchange chromatography

Abstract: Bacteriocin ST15 (bacST15), produced by Enterococcus mundtii ST15, inhibited the growth of a variety of bacteria, including exopolysaccharide (EPS)-producing strains isolated from biofilms in stainless steel pipes. Maximal production of bacST15 (51200 AU/ml) was recorded after 20 h of growth in MRS broth (Biolab), which was maintained throughout fermentation. Only 12800 AU/ml bacST15 has been recorded in MRS filtrate with components smaller than 8000 Da, suggesting that nutrients larger than 8000 Da are requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The activity against E. faecalis ATCC 19443 presented by the proteins precipitated with ammonium sulfate and reconstituted in ammonium acetate buffer was similar to that presented by the fractions after chromatography on SepPak C 18 column and elution with 40, 60 or 80% iso-propanol (1.0 × 10 8 AU/mL). A similar purification protocol was used for purification of bacteriocins produced by another L. plantarum and Enterococcus mundtii (Granger, Todorov, Matthew, & Dicks, 2005;Todorov, Wachsman, Knoetze, Meincken, & Dicks, 2005;Todorov et al, 1999).…”
Section: Partial Purification Of Bacteriocin St16pamentioning
confidence: 99%
“…The activity against E. faecalis ATCC 19443 presented by the proteins precipitated with ammonium sulfate and reconstituted in ammonium acetate buffer was similar to that presented by the fractions after chromatography on SepPak C 18 column and elution with 40, 60 or 80% iso-propanol (1.0 × 10 8 AU/mL). A similar purification protocol was used for purification of bacteriocins produced by another L. plantarum and Enterococcus mundtii (Granger, Todorov, Matthew, & Dicks, 2005;Todorov, Wachsman, Knoetze, Meincken, & Dicks, 2005;Todorov et al, 1999).…”
Section: Partial Purification Of Bacteriocin St16pamentioning
confidence: 99%
“…Similar purification protocol was used by other researchers for purification of bacteriocins produced by Lactobacillus plantarum and Ent. mundtii (Todorov et al, 1999(Todorov et al, , 2004(Todorov et al, , 2005Granger et al, 2005).…”
Section: Purification Of Bacteriocin St5hamentioning
confidence: 99%
“…Several authors have indicated that optimal culture conditions are strain dependent and should be adjusted for each microorganism (Mataragas et al, 2003;De Vuyst and Leroy, 2007;Settanni et al, 2008). Some bacteriocin-producing E. mundtii strains isolated mainly from vegetables matrices have been described and proposed for the biopreservation of plant-related foods (Granger et al, 2005;Zendo et al, 2005;Settanni et al, 2008). Enterococcus mundtii CRL35, a strain isolated from an artisanal cheese, produces enterocin CRL35, which exerts an inhibitory effect on the growth of spoilage and pathogenic microorganisms (Salvucci et al, 2012;Vera Pingitore et al, 2012).…”
Section: Introductionmentioning
confidence: 99%